Tissue and Age Specificity of Aqueous-Saline Extracts from Cryopreserved Xenoorgans Fragments - Galchenko, S. E. (Problems of Cryobiology and Cryomedicine, 2005)
The molecular mass distribution of peptides in water-saline extracts from cryopreserved xenoorgans fragments was studied in this work using the chromatographic method. It was shown that it depended on both kind of organ and the animal age. The data obtained can find application in investigating the mechanisms of biological action of these extracts as well as for working out the preparations on their basis.